The Effect of Audit Findings, Follow-Up Audit Recommendations, And BPK Opinions from The Previous Year on The Determination of Opinions in Local Government Financial Statements - Rena Mainingrum; Sylvia Sjarlis; Andi Ririn Oktaviani; Reno Fithri Meuthia (International Ecsis Association, 2023)
This study aims to analyze the effect of audit findings, follow-up on audit recommendations from the Supreme Audit Agency (BPK RI) and audit opinion from previous year on the determination of audit opinions on local government financial statements. The historical data of 24 local governments in South Sulawesi for the period 2016 - 2020 related to the examination of local government financial statements is used in this study. The results of the study found that: 1) There was a positive but not significant effect on the opinion of the Audit Findings on the determination of the audit opinion of the district government in South Sulawesi, 2) there was a positive and significant effect of follow-up on the recommendations of the audit results of local government in South Sulawesi, and 3) there was a negative and significant effect of the previous year audit opinion on the opinion of the local government financial statements.